Science of fat - Ronald M. Evans, lecturer; Jeffrey M. Friedman, lecturer; Howard Hughes Medical Institute (Chevy Chase, MD Howard Hughes Medical Institute, 2005)
In four thought-provoking presentations, Dr. Ronald M. Evans and Dr. Jeffrey Friedman discuss the complex biological systems that control body weight and energy metabolism--and how a better genetic understanding of these processes could lead researchers to treatments that curb obesity and improve public health.
Disc 1 -- Lecture 1. Deconstructing obesity / Jeffrey M. Friedman -- Lecture 2. Understanding fat : syndrome X and beyond / Ronald M. Evans -- Lecture 3. Balancing the fat equation / Ronald M. Evans -- Lecture 4. Exploring obesity : from the depths of the brain to the far Pacific / Jeffrey M. Freidman -- Disc 2. Discussion sessions and interviews.
Howard Hughes Medical Institute holiday lectures on science, December 2004.
Keywords: Obesity; Obesity -- Physiological aspects; Obesity -- etiology; Obesity -- prevention & control; Body Weight -- physiology